Crime as structured action : gender, race, class, and crime in the making - Messerschmidt, James W. (Sage Pub, 1997)
The author of this volume skillfully demonstrates that a vital component to understanding crime is to be able to view it as more than a single activity. James W. Messerschmidt argues that crime operates subtly through a complex series of gender, race and class practices and these interwoven elements must be seen as part of all social existence, not viewed independently.